Journal Overlap of the Meteorological & Geoastrophysical Abstracts and Web of Science Databases. Issue 2 (3rd April 2018) - Kimball, Rusty
ABSTRACT: A journal overlap analysis was performed between the academic library databases Meteorological & Geoastrophysical Abstracts (MGA) and Web of Science. This overlap analysis determined that there are 1263 serial titles common to both Web of Science and MGA with a full 87 percent of the 1447 MGA journals/serials indexed in Web of Science. In all, 5.47 percent of Web of Science journals are indexed in MGA. The size of this overlap may have potential implications for library collections.